AB1168 SIGLEC1/CD169 IS A SENSITIVE MARKER FOR MONOGENIC INTERFERONOPATHIES. (June 2019) - Orak, Banu; Nikolaus, Marc; Knierim, Ellen; Kaindl, Angela; Theophil, Manuela; Panzer, Axel; Zieba, Barbara; Ebstein, Frédéric; Krüger, Elke; Unterwalder, Nadine; Meisel, Christian; Kallinich, Tilmann
Abstract : Background: Monogenic Interferonopathies are a rare group of inflammatory diseases that are difficult to diagnose in the onset phase given the lack of well-defined disease-markers. 1 A correlation with interferon-stimulated genes (ISG) has been reported for SIGLEC1 (syn. CD169), in systemic lupus erythematodes (SLE). 2 Furthermore, expression of SIGLEC1 on monocytes is the second highest ISG in SLE. 3 Objectives: To study the relevance of SIGLEC1 as a putative diagnostic marker for early detection of interferonopathies. Methods: Clinical data, classical inflammatory markers, blood count values and genetic information were obtained from the medical files of eight patients with genetically confirmed monogenic interferonopathies. SIGLEC1 expression was measured by flow cytometry with a highly standardized quantitative assay with a reference range in healthy controls less than 2500 SIGLEC1 molecules/monocyte. Additionally, transcriptional level of SIGLEC1, IFI44L, IFI27, ISG15 and RSAD2 as type I Interferon stimulated genes were assessed by real-time PCR. Results: All eight patients with interferonopathies carried mutations in the genes TREX -1 (n=3), IFIH -1 (n=2), SAMDH1 (n=2) and RNASE2HB (n=1). Mean age of patients was 12 years (range 6 months to 49 years). Six of eight patients showed neurological symptoms consistent with Aicardi-Goutieres-Syndrome presenting developmental delay and microcephaly. Five patients showed abnormalities on cranial MRI including periventricular calcifications and corpus callosum thinning. Two patients were diagnosed with Singleton-Merten-Syndrome presenting abnormal ossification of extremities and dental anomalies. One patient with homozygous TREX1 mutation presented with postnatal glaucoma, microcephaly, sensorimotor polyneuropathia and recurrent fever with persistent chilblain lesions. All patients had elevated SIGLEC1 levels (mean molecules/monocyte +/- SD: 10272 +/- 3746) without high levels of standard inflammatory markers. In six patients, elevated SIGLEC1 expression showed dysregulation of the type 1 interferon pathway prior to genetic testing. The relative expression (ΔCt) of all ISG's was significantly elevated in comparison to healthy controls ( SIGLEC1 p= 0, 0167, ISG15 p=0, 0015, RSAD2 p=0, 0067, IFIL44 p=0, 0001, IFI27 p=0, 0056). Conclusion: We report high expression of SIGLEC1 in monogenic interferonopathies like Aicardi-Goutières-Syndrome. Therefore, SIGLEC1 qualifies as an easy accessible and cheap diagnostic marker to screen patients with suspected interferonopathy. References: [1] Crow, Y.J., Type I interferonopathies: mendelian type I interferon up-regulation. Curr Opin Immunol, 2015. 32: p. 7-12. [2] Rose, T., et al., Are interferon-related biomarkers advantageous for monitoring disease activity in systemic lupus erythematosus? A longitudinal benchmark study. Rheumatology (Oxford), 2017. 56(9): p. 1618-1626. [3] Biesen, R., et al., Sialic acid-binding Ig-like lectin 1 expression in inflammatory and resident monocytes is a potential biomarker for monitoring disease activity and success of therapy in systemic lupus erythematosus. Arthritis Rheum, 2008. 58(4): p. 1136-45. Disclosure of Interests: Banu Orak: None declared, Marc Nikolaus: None declared, Ellen Knierim: None declared, Angela Kaindl: None declared, Manuela Theophil: None declared, Axel Panzer: None declared, Barbara Zieba: None declared, Frédéric Ebstein: None declared, Elke Krüger: None declared, Nadine Unterwalder: None declared, Christian Meisel: None declared, Tilmann Kallinich Grant/research support from: Novartis, Speakers bureau: Sobi, Roche, Novartis, CLB